Inhibition of Fungal Growth and Induction of a Novel Volatilome in Response to Chromobacterium vaccinii Volatile Organic Compounds - Ebadzadsahrai, Ghazal; Higgins Keppler, Emily A.; Soby, Scott D.; Bean, Heather D. (Frontiers in Microbiology, 2020)
The study of chemical bioactivity in the rhizosphere has recently broadened to include microbial metabolites, and their roles in niche construction and competition via growth promotion, growth inhibition, and toxicity. Several prior studies have identified bacteria that produce water-soluble or volatile organic compounds (VOCs) with antifungal activities, indicating their potential use as biocontrol organisms to suppress phytopathogenic fungi and reduce agricultural losses. We sought to expand the roster of soil bacteria with known antifungal properties by screening 68 bacterial isolates from wild and cultivated cranberry bog soils for organic compounds that inhibit the growth of four common fungal and oomycete plant pathogens, and Trichoderma sp. A quarter of the screened isolates inhibited the growth of at least one fungus by the production of soluble and/or volatile organic compounds. Isolates of Chromobacterium vaccinii had broad antifungal activity via production of both soluble and volatile compounds, with VOC growth inhibition as high as 90% for some fungi. Fungi exposed to C. vaccinii VOCs had extensive morphological abnormalities such as swollen hyphal cells, vacuolar depositions, and cell wall alterations. Quorum-insensitive cviR- mutants of C. vaccinii were significantly less fungistatic, indicating a role for quorum regulation in the production of antifungal compounds. We collected and characterized volatiles from co-cultivation assays of Phoma sp. exposed to wild-type C. vaccinii MWU328, and its cviR- mutant using stir bar sorptive extraction and comprehensive two-dimensional gas chromatography – time-of-flight mass spectrometry (SBSE-GC×GC-TOFMS), and detected 53 VOCs that differ significantly in abundance between microbial cultures and media controls, including three candidate quorum-regulated fungistatic VOCs produced by C. vaccinii. Additionally, the metabolomes of the bacterial-fungal co-cultures were not the sum of the mono-culture VOCs, an emergent property of their volatile-mediated interactions. These data suggest semiochemical feedback loops between the microbes that have co-evolved for sensing and responding to exogenous VOCs.